THE INFLUENCE OF LEADERSHIP, MOTIVATION ON LOYALTY AND EMPLOYEE PERFORMANCE OF PT. BENTORO ADISANDI IVENA PEKANBARU - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 5 No 2 (2025): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine the influence of leadership, motivation on loyalty and performance of PT. Bentoro Adisandi Ivena Pekanbaru. The sample of this study is all employees at PT. Bentoro Adisandi Ivena Pekanbaru with 42 employees. Data analysis uses Path analysis to analyze the pattern of relationships between variables with the aim of knowing the direct and indirect effects of independent variables (leadership and motivation) on the dependent variables (employee loyalty and performance). The results of the study with regression showed two variables that had a significant effect, namely leadership had a significant effect on performance and motivation had a significant effect on loyalty while leadership had no effect on loyalty, motivation did not affect performance, and loyalty did not affect performance. The findings of leadership research have no effect on performance if through loyalty remains leadership has a significant effect on performance directly and motivation has a significant effect directly on loyalty. This research suggests for companies to increase motivation, training and provide work comfort so that employees feel comfortable with the encouragement of employee motivation and training so that employee performance is better than before.